2014
DOI: 10.2337/dc13-1658
|View full text |Cite
|
Sign up to set email alerts
|

CDH13 Genotype–Dependent Association of High–Molecular Weight Adiponectin With All-Cause Mortality: The J-SHIPP Study

Abstract: OBJECTIVEDespite its anti-inflammatory and antiatherogenic effects, adiponectin is potentially associated with adverse clinical outcomes, such as all-cause mortality. As plasma adiponectin levels are strongly influenced by single nucleotide polymorphisms in the gene encoding T-cadherin (CDH13), we conducted a longitudinal study to investigate the possible link between the CDH13 genotype, plasma adiponectin levels, and all-cause mortality. RESEARCH DESIGN AND METHODSThis longitudinal study evaluated 2,020 Japan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…T-cad-deficient mice exhibited elevated levels of circulating HMW-APN [11,12] and genome-wide association studies have linked variants in T-cad gene to elevated [33] or decreased [34] circulating levels of APN in humans, supporting that circulating APN is influenced by the presence and/or functionality of T-cad. Conversely, APN-deficient mice exhibited a reduced tissue level of T-cad protein that was restorable in vivo by delivery of exogenous APN [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T-cad-deficient mice exhibited elevated levels of circulating HMW-APN [11,12] and genome-wide association studies have linked variants in T-cad gene to elevated [33] or decreased [34] circulating levels of APN in humans, supporting that circulating APN is influenced by the presence and/or functionality of T-cad. Conversely, APN-deficient mice exhibited a reduced tissue level of T-cad protein that was restorable in vivo by delivery of exogenous APN [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…total APN or HMW-total ratio) [4951] have been demonstrated, and in the context of cardiovascular protective actions HMW-APN is regarded as the active form of this adipokine [49,51,52]. Additionally, in the context of associations between T-cad and APN a number of genome-wide studies revealed that association of SNPs in CDH13 gene were much stronger with levels of HMW-APN as compared total APN levels [33,53]. Fourth, and with regard to gender-issues, levels of testosterone and estradiol were not measured.…”
Section: Discussionmentioning
confidence: 99%
“…CAD coronary artery disease, LDL low-density lipoprotein, SBP systolic blood pressure. a Wallace et al ( 2008 ); b Org et al ( 2009 ), Fava et al ( 2011 ), Wan et al ( 2013 ); c Jee et al ( 2010 ); d Jee et al ( 2010 ), Wu et al ( 2010 ), Jo et al ( 2012 ); e Jee et al ( 2010 ), Chung et al ( 2011 ); f Lee et al ( 2013 ); g Chung et al ( 2011 ), Morisaki et al ( 2012 ), Gao et al ( 2013 ), Uetani et al ( 2014 ); h Morisaki et al ( 2012 ), Dastani et al ( 2012 ); i Dastani et al ( 2012 ); j Lee et al ( 2013 ); k Wellcome Trust Case Control Consortium ( 2007 ); l Ling et al ( 2009 ); m Levy et al ( 2007 ) …”
Section: Introductionmentioning
confidence: 99%
“…The subjects attended a voluntary medical check-up program, Anti-Aging Doc, a program provided to residents of Ehime Prefecture, Japan, specifically designed to evaluate aging-related disorders, including atherosclerosis, cardiovascular disease, physical function, and cognitive impairment. 6,[18][19][20][21] Of the 1526 consecutive patients initially approached, 1296 (mean age, 65.4±9.1 years) gave written consent to all procedures and had no history of symptomatic cardiovascular events including peripheral arterial disease, stroke, coronary heart disease, or congestive heart failure. All participants were functionally independent in their daily lives.…”
Section: Subjectsmentioning
confidence: 99%